2021
DOI: 10.3389/fmars.2021.741912
|View full text |Cite
|
Sign up to set email alerts
|

Study of Heavy Metals and Microbial Communities in Contaminated Sediments Along an Urban Estuary

Abstract: Estuarine sediments are increasingly contaminated by heavy metals as a result of urbanization and human activities. Continuous multi-heavy metal accumulation in the ecosystem can provoke new effects on top of the complex environmental interactions already present in estuarine ecosystems. It is important to study their integrated influence on imperative microbial communities to reflect on the environmental and ecological risks they may impose. Inductively coupled plasma optical emission spectroscopy analysis fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 56 publications
(61 reference statements)
1
6
0
Order By: Relevance
“…Other important phyla observed in this study are, Actinobacterota, Planctomycetota, Acidobacteriota, Gemmatimonadota, Myxococcota, and Halobacteriota (Archaea) as the most abundant. All the abundant microbial phyla obtained in this study have been documented previously in other metal-contaminated environments, such as sediments (Lee et al, 2021;Rajeev et al, 2021;Yi et al, 2021;Custodio et al, 2022), iron tailing pond (Li et al, 2021), mining soils (Cao et al, 2017;Hemmat-Jou et al, 2018;Liu et al, 2021a), paddy soils (Tseng et al, 2021), arid loess region (Zeng et al, 2020), and electric waste soils (Jiang et al, 2019), this suggests that these phyla are associated with metal-polluted sediment.…”
Section: B a Figure 10supporting
confidence: 84%
“…Other important phyla observed in this study are, Actinobacterota, Planctomycetota, Acidobacteriota, Gemmatimonadota, Myxococcota, and Halobacteriota (Archaea) as the most abundant. All the abundant microbial phyla obtained in this study have been documented previously in other metal-contaminated environments, such as sediments (Lee et al, 2021;Rajeev et al, 2021;Yi et al, 2021;Custodio et al, 2022), iron tailing pond (Li et al, 2021), mining soils (Cao et al, 2017;Hemmat-Jou et al, 2018;Liu et al, 2021a), paddy soils (Tseng et al, 2021), arid loess region (Zeng et al, 2020), and electric waste soils (Jiang et al, 2019), this suggests that these phyla are associated with metal-polluted sediment.…”
Section: B a Figure 10supporting
confidence: 84%
“…It seems that environmental factors that influence the fungal microbiome composition are different from those that impact bacterial microbiomes [ 58 ]. For example, for contaminated soils and sediments, studies have shown that bacterial and fungal communities may exhibit differences in their response to heavy metals [ 59 , 60 , 61 , 62 , 63 , 64 ]. This is partly based on common differences in the biochemical pathways activated by bacteria and fungi in response to heavy metals and PAHs [ 65 , 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations of polluted soils and sediments suggested that microorganism exposure to HM follows precise ecotoxicological rules [51]- [53]. However, it is currently thought that HM induce different responses in bacterial and fungal communities [54], [55].…”
Section: Introductionmentioning
confidence: 99%